Reduction in Public Forest Productivity (The Common Natural Resource Capital) of the Country- Its Negative Effects on Livelihood Potential of Forest; A Case Study from Jharkhand - Gupta, H. S.; Sinha, V. K.; Bala, S. (Indian Forester, 2024)
Implementation of the STOFDRA 2006 in (called in short as FRA), India started as an opportunity of study the value issues affecting security of tenurial and access rights of the indigenous communities and its possible effect on better conservation of forest resources. Thus, this statute is based on premise that while ensuring livelihood and food security of the beneficiary individuals/community by giving the rights in the forest, will result in sustainable use and strengthening the conservation practices for forest/biodiversity by the beneficiaries. The study attempts to monitor this aspect of FRA. However, the right of individual occupation for self-cultivation is by far the most dominant rights by the individuals-has been the most exercised so far, as seen in the practice. Though a range of operational Policies and processes have been built in to implement the said statutory rights, yet in a sizeable number of cases it has been obviated and thus negating the basic conservation related objectives of the FRA, resulting in perverted outcomes. Analysis of a case study regarding recognition of such rights in Jharkhand State illustrate that how the process is availed and dominated by eagerness to bring large forest areas under cultivation of agricultural crops and that overlooks spill over adverse impact on ecosystem qualities of not only the â€œPatta landâ€ but it also degrades the adjoining ecosystem in the vicinity of â€œPatta landsâ€. Further assessing validity of individual claims illustrate shift towards use of subjective and error-prone criteria is resulting in recognition of rights in many incongruous cases. The, deterioration is surrounding forest and around the Patta land was noticed-wherein all 32 grants were found with deviations, involving around 25.42% of additional area of adjoining forests adversely usurped by the individual beneficiary, beside affecting 22.5% reduction in forest / tree cover in vicinity of such grant plots too, depriving the interests of majority of forest dependents community. The study further also shows assertion of invalid and imaginary socioeconomic rights during and after the recognition, prevailing over equitable and sustainable forest management by ignoring the well-structured implementation practice. As a consequence, balance between ecological and socio-economic elements of Forest management remains elusive in policy performance of this statute. It is apprehended that as a consequence, the society may face serious threat to ecological integrity to the Commons Forest ecosystem of the country and associated loss of carbon sequestration and other ecosystem services etc. and the resultant livelihood potential would also be adversely affected, if faulty implementation of FRA continues. Hence it requires a serious quality monitoring of the process and achievement of desired outcomes.